Effects and detection of Nandrosol and ractopamine administration in veal calves. (15th April 2017) - Divari, Sara; Berio, Enrica; Pregel, Paola; Sereno, Alessandra; Chiesa, Luca; Pavlovic, Radmila; Panseri, Sara; Bovee, Toine F.H.; Biolatti, Bartolomeo; Cannizzo, Francesca T.
Highlights: Androgens and β-agonists are growth promoters illegally used in farm animals. Testes, sex accessory glands, skeletal muscle are target organs of these molecules. Myosin heavy chain of Longissimus dorsi muscle of treated animals is up-regulated. Indirect and direct methods of analysis can be flanked to detect illicit treatment. Abstract: The present study describes different effects of the selective androgen receptor modulator (SARM) nandrolone phenylpropionate (Nandrosol) and the β-agonist ractopamine administration in veal calves, and it investigates different strategies applied to trace these molecules. Morphological changes of gonads and accessory glands attributed to androgen effects, such as testicular atrophy, seminiferous tubule diameter reduction and hyperplasia of prostate epithelium, were detected, although SARMs are not described to cause these lesions. The gene expression analysis showed an anabolic activity of Nandrosol in Longissimus dorsi muscle, where myosin heavy chain (MYH) was significantly up-regulated. An IGF1 increase was weakly significant only in Vastus lateralis muscle. In conclusion, the anatomo-histopathological observations and the MYH mRNA up-regulation in Longissimus dorsi muscle confirm the androgenic treatment in experimental animals. The biosensor assay was not enough sensitive to detect residues in urines and only the direct chemical analysis of urine samples confirmed both β-agonist and SARM treatment.